2015
DOI: 10.1109/tbme.2015.2449320
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Novel Fixation Mechanism for a Transcatheter Pacemaker

Abstract: This fixation technology provides a novel solution to enable the attachment of a transcatheter pacemaker directly within the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…It has been shown that at least two tines must be applied to minimize dislodgement of the device, which may occur due to the cardiac activity. 10 However, there Major complications 0 (0%) 0 (0%)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that at least two tines must be applied to minimize dislodgement of the device, which may occur due to the cardiac activity. 10 However, there Major complications 0 (0%) 0 (0%)…”
Section: Discussionmentioning
confidence: 99%
“…11,12 To achieve sufficient fixation to the myocardium with two tines, the tines must be attached perpendicular to the myocardial wall. 10 If the tines are leaning against the myocardial wall, they do not provide enough force to secure the device; thus, the device may shift with an increase in cardiac rhythm, such as during exercise. Therefore, slight movements between the myocardium and the device could result in micro-dislodgement.…”
Section: Discussionmentioning
confidence: 99%
“…The flexibility of the nitinol tines has facilitated the ability to retrieve the device without counter-traction. 4 …”
Section: Discussionmentioning
confidence: 99%
“…The current approved indications for leadless pacing are chronic atrial tachyarrhythmia with advanced atrioventricular (AV) block; advanced AV block with low level of physical activity or short expected lifespan; and infrequent pauses or unexplained syncope with abnormal fi ndings at electrophysiologic study. Although differ-ences exist between Nanostim and Micra, as shown in Table 1, [21][22][23][24][25][26][27] there are fundamental similarities. Both are single-unit designs encapsulating the electrodes and pulse generator with rate-adaptive functionality.…”
Section: Kiehl and Cantillon ■ Leadless Pacing Technologymentioning
confidence: 99%
“…Both are delivered via an endovascular femoral venous approach without the need for incisional access, transvenous leads, or surgical pocket (Figures 3 and 4). [21][22][23][24][25][26][27] Nanostim: Landmark trials As the world's fi rst-in-man leadless pacemaker, Nanostim was evaluated in two prospective, nonrandomized, multicenter, single-arm trials abbreviated LEADLESS 22 and LEADLESS II. 24 The fi rst human feasibility study, LEADLESS, enrolled 33 patients with approved indications for ventricularonly pacing while excluding patients with expected pacemaker dependency.…”
Section: Kiehl and Cantillon ■ Leadless Pacing Technologymentioning
confidence: 99%